The susceptibility of the kidney to alternative pathway activation—A hypothesis. Issue 1 (12th November 2022) - Thurman, Joshua M.; Harrison, Richard A.
Summary: The glomerulus is often the prime target of dysregulated alternative pathway (AP) activation. In particular, AP activation is the key driver of two severe kidney diseases: atypical hemolytic uremic syndrome and C3 glomerulopathy. Both conditions are associated with a variety of predisposing molecular defects in AP regulation, such as genetic variants in complement regulators, autoantibodies targeting AP proteins, or autoantibodies that stabilize the AP convertases (C3‐ and C5‐activating enzymes). It is noteworthy that these are systemic AP defects, yet in both diseases pathologic complement activation primarily affects the kidneys. In particular, AP activation is often limited to the glomerular capillaries. This tropism of AP‐mediated inflammation for the glomerulus points to a unique interaction between AP proteins in plasma and this particular anatomic structure. In this review, we discuss the pre‐clinical and clinical data linking the molecular causes of aberrant control of the AP with activation in the glomerulus, and the possible causes of this tropism. Based on these data, we propose a model for why the kidney is so uniquely and frequently targeted in patients with AP defects. Finally, we discuss possible strategies for preventing pathologic AP activation in the kidney.